The Psychology of Saving : How Mindset Impacts Financial Competence - Fauzi, Ahmad; Fauziah, Nadiatullah Tsuraya; Rahayu, Sari (Coopetition : Jurnal Ilmiah Manajemen, 2024)
This study investigates the dynamics of financial competence among customers and employees of Bank BNI, focusing on the roles of mindset, saving behavior, and financial knowledge. Using a quantitative research design with a sample size of 100 participants selected through random sampling, data were analyzed using Smart PLS for path analysis. The findings reveal significant direct relationships: mindset positively influences both financial knowledge (FK) and financial competence (FC), while saving behavior directly enhances FC. Additionally, indirect effects show that both mindset and saving behavior contribute to FC through their positive impacts on FK. These results highlight the critical importance of psychological factors and proactive financial behaviors in shaping individuals' financial capabilities. For Bank BNI, promoting a positive financial mindset and supporting disciplined saving practices could effectively enhance financial literacy and decision-making among stakeholders. Future research could explore additional variables and interventions to further refine strategies for fostering financial competence across diverse demographic groups.